Effects of senescence and angiotensin II on expression and processing of amyloid precursor protein in human cerebral microvascular endothelial cells - Sun, Ruohan (Aging (Albany NY), 2018)
The present study was designed to determine the effects of senescence and angiotensin II (Ang II) on expression and processing of amyloid precursor protein (APP) in human brain microvascular endothelial cells (BMECs). Senescence caused a decrease in APP expression thereby resulting in reduced secretion of soluble APPα (sAPPα). In contrast, β-site APP cleaving enzyme (BACE1) expression and production of amyloid β (Aβ)40 were increased in senescent endothelium. Importantly, in senescent human BMECs, treatment with BACE1 inhibitor IV inhibited Aβ generation and increased sAPPα production by enhancing a disintegrin and metalloprotease (ADAM)10 expression. Furthermore, Ang II impaired expression of ADAM10 and significantly reduced generation of sAPPα in senescent human BMECs. This inhibitory effect of Ang II was prevented by treatment with BACE1 inhibitor IV. Our results suggest that impairment of α-processing and shift to amyloidogenic pathway of APP contribute to endothelial dysfunction induced by senescence. Loss of sAPPα in senescent cells treated with Ang II exacerbates detrimental effects of senescence on APP processing. Notably, inhibition of BACE1 has beneficial effects on senescence induced endothelial dysfunction. Reported findings may help to explain contributions of senescent cerebral microvascular endothelium to development of cerebral amyloid angiopathy and Alzheimer’s disease (AD) pathology.